U.S. Strategy in Indo Pacific in The Battle of U.S. – China Competition - Ujang Priyono (UNIVERSITAS PGRI YOGYAKARTA, 2022)
Abstract The purpose: To get more clearer understanding about U.S. foreign policy, I try to research about U.S. foreign policy in Indo Pacific. Why I choose Asia Pacific as a case, there is an interesting situation that occur in Asia Pacific region, that’s related with U.S. foreign policy. The conclusion: With AUKUS, U.S. will strengthening its relations with U.K. and Australia, although with this trilateral cooperation, the U.S. is still become the leader of this cooperation. It will be used by U.S. to run its foreign policy in Indo Pacific. Especially to face the rising China. This trilateral cooperation describe the U.S. intention to control and manage Indo Pacific region by its policy. Keyword: Strategy, Indo Pacific, U.S. Competition